Duodenal eosinophilia and early satiety in functional dyspepsia: Confirmation of a positive association in an Australian cohort. Issue 3 (March 2014) - Walker, Marjorie M; Aggarwal, Kavita R; Shim, Lisa SE; Bassan, Milan; Kalantar, Jamshid S; Weltman, Martin D; Jones, Michael; Powell, Nicholas; Talley, Nicholas J
Abstract Background and Aim Functional dyspepsia (FD), defined by unexplained pain or discomfort centered in the upper abdomen, is common. Diagnosis and treatment of FD based on the symptom‐based Rome criteria remains challenging. Recently, eosinophilia in the duodenum has been implicated in the pathophysiology of FD in adults, specifically increased eosinophils in early satiety and postprandial distress, but the association remains controversial. The aim of this study was to characterize upper gastrointestinal (GI) tract pathology, specifically duodenal eosinophilia, in an Australian cohort of patients with FD. Methods Patients prospectively referred for an upper GI endoscopy (n = 55; mean age, 49.6 years; 61.8% female) were stratified to FD cases (n = 33) and controls (n = 22) using Rome II criteria. All subjects completed a validated bowel symptom questionnaire. The eosinophil count per square millimeter in the duodenal bulb (D1) and second part (D2) was assessed and Helicobacter pylori status determined by gastric histology. Associations with clinical symptoms were assessed. Results Cases and controls were demographically similar. Duodenal eosinophilia was significantly increased in subjects experiencing early satiety (P = 0.01) and postprandial fullness (P = 0.001). This association was seen in D2 but not D1. Abdominal pain was associated with eosinophilia in both D1 (P = 0.02) and D2 (P = 0.005). Smoking was also associated with higher eosinophil counts in D2 (P = 0.007) and symptoms of early satiety (P = 0.02). Conclusions Duodenal eosinophilia occurs in a subset of FD. The potential role of duodenal eosinophils in FD has implications for diagnosis and therapeutic trials.